COHABITATION IN THE OCCUPIED PALESTINE’S POLITICAL SYSTEM - YAtiban, Aminurraasyid; Odah, Ramzi; P. Rajanthiran, R. Sivaperegasam (Journal of Al-Tamaddun, 2017)
This article attempts to investigate the impact of the mixed electoral system on the creation of the state of cohabitation that occurred in the Palestinian political system after the second legislative elections in 2006, viewed through a theoretical framework based on the idea of divided societies. This study employed quantitative and qualitative research methods together. This study found several important results regarding this relationship. Firstly, cohabitation is more likely to occur when there is a low rate of party fractionalization (more polarization) produced in the mixed electoral system. Second, the strategic voting in this election was sensitive to the divided attitudes about the Israeli occupation. Third, the mixed electoral system did not greatly reduce the small parties punishment caused by the pluralistic system, which increased opportunities for creating a state of cohabitation